MOTIVASI INTRINSIK DAN EXTRINSIK PADA PENINGKATAN KINERJA (STUDI KASUS PADA HEPI POTATO (PIPO)) - Liliana Dewi; Tamara Aurellian Thendean (Politeknik Ubaya, 2018)
This research is done with a purpose of knowing how the evaluation of the work motivation that has an impact on the performance of the members of Hepi Potato (PIPO). Methods that was used for this research is qualitative approach. The data retrieval process is done by interview method. The researcher interviewed 4 informants, they are 2 members of PIPO, a facilitator lecturer of PIPO, and a motivation expert. The aim of this research is to improve the performance of the members of PIPO by evaluating their work motivation. Based on the result of the interview, it has been found that the performance of PIPO was already good enough but has not maximum yet so it still can be improved, while for the valuation of the work motivation in PIPO decreased because of the rushing activity and has reached saturation point. The result of this research is that to increase the work motivation in PIPO, each member must search for internal motivation first and each member has to be open with one another so they can support each other. Other than motivation, there are other factors that can improve the performance which are direct supervisor and organizational culture.